Report of a Working Group on Forages: Sixth meeting, 6-8 March 1997, Beitostølen, Norway - Maggioni, L.; Marum, P.; Sackville-Hamilton, N. Ruaraidh; Thomas, I.; Gass, T.; Lipman, E.; European Cooperative Programme for Plant Genetic Resources (1998)
This report on forage genetic resources work in Europe begins with a review of current activities, including the core collection of Lolium, and an outline of recent international developments in issues related to plant genetic resources. Presented papers are then arranged under the following headings: European Central Forages Databases (13 papers); status of national collections (7); duplications in forages collections (2); standards for regeneration (1); collecting activities (13) and research activities (6). Appendices provide information on: forage passport descriptors; a protocol for designating primary holders of accessions; guidelines for the regeneration of accessions in seed collections of the main perennial forage grasses and legumes of temperate grasslands; germplasm holdings; and safety-duplication capacities. (Abstract © CAB ABSTRACTS, CAB International)